Influence of surface topography on early stages on steel galling of coated WC-Co hard metals. (June 2016) - Klünsner, T.; Zielbauer, F.; Marsoner, S.; Deller, M.; Morstein, M.; Mitterer, C.
Abstract: Galling, i.e. the transfer of workpiece material to tool surfaces, is an important factor known to influence both wear behaviour and loading conditions of metalworking tools such as deep-drawing, blanking or fine blanking punches or dies. The current study investigates very early stages of galling of mild steel on WC–Co hard metals coated by AlCrN-based hard coatings. Repeated dry-sliding contacts with virgin steel material were physically simulated by a ball-on-disc test setup with a virgin contact area on the ball in each lap. Special attention was paid to the influence of coating surface topography produced by coating post-treatment and the resulting distinct differences in galling behaviour. Galling initiation is illustrated by cross-sections of micrometre-sized features of transferred steel, showing their nucleation sites to be microscopic surface asperities. A layer-by-layer material transfer mechanism is indicated by the galling features' internal layered structure. The current work demonstrates a clear connection between the ratio of peaks to valleys on coating surfaces and the kinetics of the early stages of galling. A reduction of this ratio, e.g. by coating post-treatment via blasting with diamond-containing elastomer particles, leads to a reduced tendency for steel transfer to coated WC–Co hard metal surfaces. Highlights: Very early stages of galling observable on coatings in modified ball-on-disc test Ratio of peaks to valleys on coating surface determines galling behaviour. Blasting with diamond particles reduces ratio of peaks to valleys and thus galling. Surface asperities shown to be nucleation sites of layer-by-layer material transfer